A Novel Proof on the Existence of the Solution of Fractional Control Problem Governed by Burgers Equations (Journal of Partial Differential Equations, 2019)
In this study, first we give some conditions to prove that a fractional Burgersequation has a unique solution. For this aim, we define a special operator to deducethe uniqueness of the solution. Then we prove that the optimal control problem underfractional Burgers equation has at least one optimal solution.